Incidence, patterns and risk factors for injuries among Ugandan children. Issue 2 (3rd April 2018) - Batte, Anthony; Siu, Godfrey E.; Tibingana, Brenda; Chimoyi, Anne; Chimoyi, Lucy; Paichadze, Nino; Otwombe, Kennedy
ABSTRACT: There is limited epidemiological data on childhood injuries in developing countries. This study assessed the incidence, patterns and risk factors for injuries among children aged 0–5 years in Wakiso District, Uganda. To determine differences, chi-square and Wilcoxon rank sum tests were used. Risk factors were assessed using Poisson regression. Overall, information from 359 children of mean age 32 months (SD: 18.4) was collected. Annual incidence of injuries was 69.8 per 1000 children/year (95% CI 58.8–80.8). One fatal injury due to burns was reported. Incidence of injuries was less associated with being female (IRR: 0.56, 95% CI 0.34–0.90) and increasing age of the caretaker (IRR: 0.96, 95% CI 0.92–0.99). The high incidence of childhood injuries necessitates the need for interventions to reduce injuries among children.